The moderating effect of technostress between job demand and implementation of technology computer to performance - Ofanto Ofanto (Jurnal Kajian Manajemen dan Wirausaha, 2022)
Education has an important role in improving the quality of human resources to become reliable and competent. There is a negative and significant effect between job demand on technostress. There is a positive and significant effect between the implementation of technology on technostress. From the results of hypothesis testing conducted that there is a negative but not significant effect between job demand on performance. There is a positive but not significant effect between the implementation of technology on performance. There is a positive and significant influence between technostress on performance. There is a negative and significant effect between job demand on performance and technostress as a mediating variable. There is a positive and significant effect between implementation of technology on performance and technostress as a mediating variable.